2008
DOI: 10.1111/j.1600-0722.2008.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant survival rates after maxillary sinus augmentation

Abstract: Implant therapy in the atrophic posterior maxilla becomes challenging in the presence of reduced maxillary bone height. Sinus augmentation can be performed for resolving this condition prior to implant placement. The aim of this article was therefore to evaluate implant survival rates in the grafted sinus taking into account the influence of the implant surface, graft material, and implant placement timing. A systematic review of the literature was performed. Articles retrieved from electronic databases were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
180
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 40 publications
8
180
1
4
Order By: Relevance
“…[3][4][5][6] Knowledge of the anatomic structure of the area is important for this procedure. In the present study, we were able to observe the presence and location of the PSAA with CBCT scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Knowledge of the anatomic structure of the area is important for this procedure. In the present study, we were able to observe the presence and location of the PSAA with CBCT scans.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Sinus augmentation is a safe procedure with high predictability for rehabilitation of severely atrophic posterior maxillae. [3][4][5][6] The branches of the maxillary artery should be taken into consideration during sinus augmentation because of the potential risk of bleeding during the procedure owing to damage to the vascular supply in the lateral wall. 7 Assessment of the maxillary sinus anatomy is important to avoid unnecessary complications due to the close anatomical relationship of the PSAA with the Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Various bone-grafting materials are being used in sinus augmentation including freezedried bone allograft (Avila et al, 2010), bovine xenograft (Chaushu et al, 2009), and alloplastic material (Bae et al, 2010) as an alternative or supplement to autogenous bone. Sinus augmentation procedures are highly predictable, with many studies reporting over 95% success (Del Fabbro et al, 2008). However, sinus augmentation may be influenced by the choice of graft material and implant surface micromorphology (Del Fabbro et al, 2008), and controversies still exist related to the most suitable way to perform sinus augmentation.…”
Section: Various Ways To Enhance the Results Of Maxillary Sinus Augmementioning
confidence: 99%
“…Several studies have reported excellent long term survival rates for implants placed in the augmented maxillary sinuses [15,16].…”
Section: Discussionmentioning
confidence: 99%